THE IMPACT OF ISLAMIC THOUGHT ON MODERN SOCIAL MOVEMENTS: BRIDGING TRADITION AND REFORM - Amie Primarni; Khalil Zaman; Jamil Khan (Journal of Noesantara Islamic Studies, 2026)
movements, offering foundational principles on justice, equity, and social responsibility. In the contemporary context, Islamic principles have been integrated into modern social movements advocating for human rights, gender equality, and political reform, suggesting a bridge between religious tradition and progressive social reform. This intersection requires closer examination to understand the evolving role of Islamic thought in shaping these movements. This study aims to explore the impact of Islamic thought on modern social movements and analyze how it bridges tradition with reform. It seeks to understand how Islamic principles guide contemporary social activism and contribute to global movements for justice and equality. A mixed-methods approach was utilized, combining qualitative interviews with activists, scholars, and community leaders, along with document analysis of Islamic reformist texts and social movement manifestos. Data were analyzed thematically to identify key Islamic values influencing contemporary movements. The study finds that justice, equity, and social welfare are central Islamic principles driving social movements. These principles align closely with the goals of modern social activism, including gender rights and political reform. The integration of Islamic thought provides moral legitimacy and strategic guidance for these movements. Islamic thought plays a significant and dynamic role in modern social movements by offering a framework that bridges religious tradition with contemporary calls for reform.